Disease activity of lung cancer at the time of acute exacerbation of interstitial lung disease during cytotoxic chemotherapy. Issue 17 (15th July 2022) - Sekine, Akimasa; Matama, Goushi; Hagiwara, Eri; Tabata, Erina; Ikeda, Satoshi; Oda, Tsuneyuki; Okuda, Ryo; Kitamura, Hideya; Baba, Tomohisa; Satoh, Hiroaki; Misumi, Toshihiro; Komatsu, Shigeru; et al.
Abstract: Background: The prognosis of lung cancer patients with interstitial lung disease (ILD) is poor, and acute exacerbation (AE) of ILD can occur during chemotherapy as a fatal adverse event. Although AE‐ILD development is correlated with various factors, no reports are investigating the disease activity of lung cancer at the time of AE‐ILD development. Methods: All consecutive lung cancer patients with ILD who developed chemotherapy‐related AE‐ILD within 28 days after the last administration of cytotoxic chemotherapy between 2011 and 2020 were retrospectively reviewed. Results: Among 206 lung cancer patients with ILD who were treated with cytotoxic chemotherapy, 30 patients were included. The median age was 72 years and all patients were men with smoking history. Usual interstitial pneumonia (UIP) and non‐UIP patterns of ILD was observed in 17 and 13 patients. Most of AE‐ILD occurred during second‐ or later‐line (22/30, 73.3%) and developed within first or second courses during chemotherapy (19/30, 63.3%). Regarding tumor response to chemotherapy at AE‐ILD development, majority of patients (18 patients, 60.0%) experienced progressive disease and only one patient (3.3%) experienced a partial response. Notably, 27 patients (90.0%) did not exhibit any tumor shrinkage of the thoracic lesions. Conclusion: Lung cancer was uncontrolled with cytotoxic chemotherapy at the time of AE‐ILD development. Although AE‐ILD during chemotherapy has been generally discussed in terms of drug‐specific adverse effects, uncontrolled lung cancer may be also correlated with AE‐ILD development. Abstract : This study retrospectively included 30 consecutive lung cancer patients who developed acuate exacerbation (AE) of interstitial lung disease (ILD) during cytotoxic chemotherapy, and investigated the disease activity of lung cancer at the time of AE‐ILD development. Regarding change in tumor size of thoracic lesion from baseline or best response, majority of patients (18/30, 60%) experienced progressive disease. Only a patient (3.3%) presented a partial response. Notably, 27 patients (90%) did not exhibit any tumor shrinkage of the thoracic lesions. Although AE‐ILD during cytotoxic chemotherapy has been generally discussed in terms of drug‐specific adverse effects, uncontrolled lung cancer may be also correlated with AE‐ILD development.